Case study of a micro controller based power supply design failure - Rinehart, Richard J. (Knovel, 2011)
With the advent of more powerful microprocessors and microcontrollers at steadily decreasing prices in recent decades, the use of logic devices has blossomed. The feasibility of digital-based regulators and smart power supplies (which can monitor and report their own performance and health) has been amply demonstrated. Such supplies have become the status quo over less intelligent power circuitry among higher -end applications.